2020
DOI: 10.1002/iid3.395
|View full text |Cite
|
Sign up to set email alerts
|

miR‐223 improves intestinal inflammation through inhibiting the IL‐6/STAT3 signaling pathway in dextran sodium sulfate‐induced experimental colitis

Abstract: Introduction The pathogenesis of inflammatory bowel disease (IBD) has not yet been clarified and is closely related to several pro‐inflammatory factors. MicroRNA‐233 (miR‐223) might be involved in the development of IBD; however, the mechanism underlying its pathogenesis is unclear. In this study, we attempted to determine the role of miR‐223 in dextran sodium sulfate (DSS)‐induced colitis and explore the involvement of the IL‐6/STAT3 pathway in the development of intestinal mucosal inflammation. Materials and… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 21 publications
(44 reference statements)
0
20
0
Order By: Relevance
“…For example, the expression of miR-223 was significantly enhanced in the livers of high-fat diet-fed mice and overexpressed miR-223 can decrease the level of p-AKT (Zhang et al, 2020b). In experimental colitis and Kawasaki disease, overexpression of miR-223 can decrease the levels of p-STAT3 (Wang et al, 2019;Zhang et al, 2021). Furthermore, our study found that an miR-223-5p antagomir could restore the reduce the expression of p-AKT and p-STAT3 in diabetic corneas.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the expression of miR-223 was significantly enhanced in the livers of high-fat diet-fed mice and overexpressed miR-223 can decrease the level of p-AKT (Zhang et al, 2020b). In experimental colitis and Kawasaki disease, overexpression of miR-223 can decrease the levels of p-STAT3 (Wang et al, 2019;Zhang et al, 2021). Furthermore, our study found that an miR-223-5p antagomir could restore the reduce the expression of p-AKT and p-STAT3 in diabetic corneas.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the pathological process underlying IBD involves the dysregulated synthesis of pro-inflammatory cytokines. [ 35 ] Thus, it would be interesting to estimate expression of inflammatory mediators that promote leukocyte/endothelial cell adhesion such as TNF-alpha, IL-1, or IL-6 which correlates with neoplasia and autoimmune disorders[ 36 37 38 ] or signaling pathways such as nuclear factor-κB, which can be activated by TNF-alpha and IL-1beta in IBS patients. [ 39 ] Finally, expression of other adhesion molecules, namely, Syndecan-1, E-cadherin/β-catenin, and proteins related with neoangiogenesis which are known for their role in colon tumorigenesis[ 40 ] could be a field for further investigation in IBS and IBD pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, Zhang et al. (2021) observed that miR-223 agomir resulted in Bcl-2 and Bcl-xl downregulation and colonic inflammation remission in DSS-induced mice ( 81 ). Interestingly, miR-223 has been reported to be pro-inflammatory by Wang et al.…”
Section: Mirna-related Potential Therapies To Ibdmentioning
confidence: 98%